RUNOFF PRODUCTION AND EROSION PROCESSES ON A DEHESA IN WESTERN SPAIN* - Ceballos, Antonio; Cerdà, A.; Schnabel, Susanne (Geographical Review, 2010)
Runoff generation and soil erosion were investigated at the Guadalperal6n ex- perimental watershed (western Spain), within the land-use system known as dehesa, or open, managed evergreen forests. Season and type of surface were found to control runoff and soil- loss rates. Five soil units were selected as representative of surface types found in the study area: hillslope grass, bottom grass, tree cover, sheep trails, and shrub cover. Measurements were made in various conditions with simulated rainfall to gain an idea of the annual varia- tion in runoff and soil loss. Important seasonal differences were noted due to surface cover and moisture content of soil, but erosion rates were determined primarily by runoff. Surfaces covered with grass and shrubs always showed less erosion; surfaces covered with holm oaks showed higher runoff rates, due to the hydrophobic character of the soils. Concentrations of runoff sediment during the siniulations confirmed that erosion rates at the study site de- pended directly on the sediment available on the soil surface
Keywords: Dehesa; erosion; land use; rainfall simulation; runoff; Spain

Gully erosion, land use and topographical thresholds during the last 60 years in a small rangeland catchment in SW Spain - Gutiérrez, Álvaro Gómez; Schnabel, Susanne; Contador, Francisco Lavado (Land Degradation & Development, 2009)
Gully erosion plays an important role in degradation processes of Mediterranean environments. In this paper aerial orthophotographs were used for (i) analysing the evolution of a valley bottom gully and its relation with land use and vegetation cover, (ii) exploring the role of land use and vegetation cover on the coefficients of the equation S = aA−b (where S is slope at the headcut and A is drainage area), which is based on the topographical threshold concept and is commonly used to predict gully initiation. The study was carried out in a small catchment (99·5 ha) located in the southwest of the Iberian Peninsula. Gullies and headcuts were mapped together with land use and vegetation cover using aerial photographs for the years 1945, 1956, 1989, 1998, 2002 and 2006, which had to be digitized and orthorectified in advance. The results showed an increase of the area affected by gullying from 695 m2 in 1945–1009 m2 in 2006, reaching a maximum of 1560 m2 in 1956. Gullying was closely related with land use, especially with the amount of cultivated areas within the catchment and also with grazing intensity. No clear relationship was found between the evolution of the gullied area and rainfall amounts. Finally, the values of the exponent b obtained for different headcuts and different dates (close to 0·4) were similar to those proposed by other authors for gully erosion caused by Hortonian overland flow in semiarid environments. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Gully erosion; land use; orthophotographs; Overgrazing; topographical thresholds

Modelling the occurrence of gullies in rangelands of southwest Spain - Gómez Gutiérrez, Álvaro; Schnabel, Susanne; Felicísimo, Ángel M (Earth Surface Processes and Landforms, 2009)
Gully erosion has been recognized as an important soil degradation process in rangelands of southwest Spain. In this paper, a relatively new data mining technique called Multivariate Adaptive Regression Splines (MARS) was applied to construct a model capable of predicting the location of gullies. A large database was used to support the model composed of a target variable (presence or absence of gullies) and 36 independent variables related to topography, lithology, soils, rainfall, land use and vegetation cover. The performance of the model was evaluated using the Receiver Operating Characteristic (ROC) curve for ﬁ ve external datasets. The model had high predictive power, with values for the area under the ROC curve of the external validation datasets varying from 0·75 to 0·98 (1·0 being perfect prediction). The most important variables explaining the spatial distribution of gullies were lithology and soil type. Finally the model was compiled and implemented into a geographical information system to obtain maps of susceptible areas for gully erosion. These maps show that approximately 7% of the study area presents favourable conditions for the development of gullies. The results demonstrate that MARS constitutes a valuable model in geomorphic research and could also be a useful tool for assessing the impacts of changing climate and land use on gully erosion.
Keywords: Gully erosion; MARS; predictive modelling; Rangelands

Using and comparing two nonparametric methods (CART and MARS) to model the potential distribution of gullies - Gutiérrez, Álvaro Gómez; Schnabel, Susanne; Lavado Contador, J Francisco (Ecological Modelling, 2009)
Gully erosion represents an important soil degradation process in rangelands. In order to take preventive or control measures and to reduce its environmental damages and economical costs it is useful to localize the points in the landscape where gullying takes place and to determine the importance of the different factors involved. The study is carried out in Extremadura, southwest Spain. The main objectives of this work are: (a) comparing two nonparametric schemes to model the potential distribution of gullies, (b) evaluating the importance of the different factors involved in gullying processes, (c) analyzing the role of prevalence in the success of the model and ﬁnally, (d) implementing and mapping the results with the help of a Geographical Information System (GIS). Two methods were used to model the response of a dependent variable (gullying) from a set of independent variables: Classiﬁcation And Regression Trees (CART) and Multivariate Adaptive Regression Splines (MARS). Three different datasets were used; the ﬁrst one for constructing the model (training dataset) and the others for validating the model (external datasets). These datasets are formed by a target variable (presence or absence of gullies) and a set of independent variables. The dependent variable was obtained by mapping the locations of gullies with the help of a GPS and high resolution aerial ortophotographs. A set of 32 independent variables reﬂecting topography, lithology, soil type, climate, land use and vegetation cover of each area were used. The performance of the models was evaluated using a non-dependent threshold method: the Receiver Operating Characteristic (ROC) curve. The results showed a better performance of MARS for predicting gullying with areas under the ROC curve of 0.98 and 0.97 for the validation datasets, while CART presented values of 0.96 and 0.66.
Keywords: CART; Gully erosion; MARS; Nonparametric modelling; Rangelands; ROC curve

Using and comparing two nonparametric methods (CART and MARS) to model the potential distribution of gullies - Gutiérrez, Álvaro Gómez; Schnabel, Susanne; Lavado Contador, J. Francisco (Ecological Modelling, 2009)
Gully erosion represents an important soil degradation process in rangelands. In order to take preventive or control measures and to reduce its environmental damages and economical costs it is useful to localize the points in the landscape where gullying takes place and to determine the importance of the different factors involved. The study is carried out in Extremadura, southwest Spain. The main objectives of this work are: (a) comparing two nonparametric schemes to model the potential distribution of gullies, (b) evaluating the importance of the different factors involved in gullying processes, (c) analyzing the role of prevalence in the success of the model and ﬁnally, (d) implementing and mapping the results with the help of a Geographical Information System (GIS). Two methods were used to model the response of a dependent variable (gullying) from a set of independent variables: Classiﬁcation And Regression Trees (CART) and Multivariate Adaptive Regression Splines (MARS). Three different datasets were used; the ﬁrst one for constructing the model (training dataset) and the others for validating the model (external datasets). These datasets are formed by a target variable (presence or absence of gullies) and a set of independent variables. The dependent variable was obtained by mapping the locations of gullies with the help of a GPS and high resolution aerial ortophotographs. A set of 32 independent variables reﬂecting topography, lithology, soil type, climate, land use and vegetation cover of each area were used. The performance of the models was evaluated using a non-dependent threshold method: the Receiver Operating Characteristic (ROC) curve. The results showed a better performance of MARS for predicting gullying with areas under the ROC curve of 0.98 and 0.97 for the validation datasets, while CART presented values of 0.96 and 0.66.
Keywords: CART; Gully erosion; MARS; Nonparametric modelling; Rangelands; ROC curve

Temporal instability of parameters in an event-based distributed hydrologic model applied to a small semiarid catchment - Maneta, Marco P; Pasternack, Gregory B; Wallender, Wesley W; Jetten, Victor; Schnabel, Susanne (Journal of Hydrology, 2007)
Event-based hydrologic modeling is common practice for semiarid basins where runoff is restricted to short periods after a storm. Such models are used to predict runoff production and soil erosion in agricultural areas as well as the effects of storms on sewer systems, all in areas with limited information. Sometimes, model parameterization is done through inﬁltration experiments to obtain a parametric inﬁltration curve or using standard values in lookup tables associated with land use as it is often the case for hydraulic roughness. The model may then be used to predict soil losses or runoff production in storms of different intensities. In the present study a distributed hydrologic model was calibrated to see if rainfall–runoff events of different intensities in a single semiarid basin may have different optimal calibrated sets of parameters. To achieve this, 17 sequential events were calibrated covering a wide range of conditions and storm types in the semiarid southwest of Spain. Two parameters related to roughness (Manning’s n and standard deviation of terrain micro-heights) and three related to inﬁltration (initial and ﬁnal inﬁltration capacities and inﬁltration decay rate) were calibrated for each event. The results show that the calibrated set of parameters and their sensitivities change through time. The drift of the minima in the parameter space is partially explained by the type of storm. Hydraulic roughness and initial inﬁltration capacity showed the highest sensitivity to rainfall intensity, while steady state inﬁltration capacity showed sensitivity to information used as a proxy for the wetness state of the basin. The dynamics of the parameters and their relative sensitivities indicate that the model has to adjust itself to the different conditions of the basin so no single set of parameters characterizes the basin.
Keywords: Basin dynamics; Calibration; Distributed modeling; Parameterization; Rainfall–runoff relationship

Temporal instability of parameters in an event-based distributed hydrologic model applied to a small semiarid catchment - Maneta, Marco P.; Pasternack, Gregory B.; Wallender, Wesley W.; Jetten, Victor; Schnabel, Susanne (Journal of Hydrology, 2007)
Event-based hydrologic modeling is common practice for semiarid basins where runoff is restricted to short periods after a storm. Such models are used to predict runoff production and soil erosion in agricultural areas as well as the effects of storms on sewer systems, all in areas with limited information. Sometimes, model parameterization is done through inﬁltration experiments to obtain a parametric inﬁltration curve or using standard values in lookup tables associated with land use as it is often the case for hydraulic roughness. The model may then be used to predict soil losses or runoff production in storms of different intensities. In the present study a distributed hydrologic model was calibrated to see if rainfall–runoff events of different intensities in a single semiarid basin may have different optimal calibrated sets of parameters. To achieve this, 17 sequential events were calibrated covering a wide range of conditions and storm types in the semiarid southwest of Spain. Two parameters related to roughness (Manning’s n and standard deviation of terrain micro-heights) and three related to inﬁltration (initial and ﬁnal inﬁltration capacities and inﬁltration decay rate) were calibrated for each event. The results show that the calibrated set of parameters and their sensitivities change through time. The drift of the minima in the parameter space is partially explained by the type of storm. Hydraulic roughness and initial inﬁltration capacity showed the highest sensitivity to rainfall intensity, while steady state inﬁltration capacity showed sensitivity to information used as a proxy for the wetness state of the basin. The dynamics of the parameters and their relative sensitivities indicate that the model has to adjust itself to the different conditions of the basin so no single set of parameters characterizes the basin.
Keywords: Basin dynamics; Calibration; Distributed modeling; Parameterization; Rainfall–runoff relationship

Hydrological behaviour of a small catchment in the dehesa landuse system (Extremadura, SW Spain) - Ceballos, Antonio; Schnabel, Susanne (Journal of Hydrology, 1998)
Investigations of the hydrological processes operating in a small experimental catchment representative of the dehesa ecosystem were carried out. The dehesa constitutes a system of agro-silvo-pastoral landuse, which is characterized by a Mediterranean, semi-arid climate. The study includes an analysis of the relationships between rainfall, soil water content and discharge, as well as the establishment of the annual water budget. The results demonstrate a complex hydrological response. The relationships between the factors involved and the operating processes are difﬁcult to explain because of the decisive role played by the valley bottoms. These areas typically possess a sediment ﬁll, and contrast with the shallow soils developed on the hillslopes. Genesis and quantity of runoff (Hortonian or saturation) measured at the outlet depend on the antecedent moisture conditions of the valley bottoms because of their water-retention capacity. Annual runoff coefﬁcients are similar to those reported from other semi-arid areas. The analysis of the annual water budget shows that rainfall is positively related with both actual evapotranspiration and discharge
The following values have no corresponding Zotero field: publisher: Elsevier
Keywords: Dehesa; Runoff–rainfall relationship; Semi-arid areas; Small catchment; Water budget

Hydrological behaviour of a small catchment in the dehesa landuse system (Extremadura, SW Spain) - Ceballos, Antonio; Schnabel, Susanne (Journal of Hydrology, 1998)
Investigations of the hydrological processes operating in a small experimental catchment representative of the dehesa ecosystem were carried out. The dehesa constitutes a system of agro-silvo-pastoral landuse, which is characterized by a Mediterranean, semi-arid climate. The study includes an analysis of the relationships between rainfall, soil water content and discharge, as well as the establishment of the annual water budget. The results demonstrate a complex hydrological response. The relationships between the factors involved and the operating processes are difﬁcult to explain because of the decisive role played by the valley bottoms. These areas typically possess a sediment ﬁll, and contrast with the shallow soils developed on the hillslopes. Genesis and quantity of runoff (Hortonian or saturation) measured at the outlet depend on the antecedent moisture conditions of the valley bottoms because of their water-retention capacity. Annual runoff coefﬁcients are similar to those reported from other semi-arid areas. The analysis of the annual water budget shows that rainfall is positively related with both actual evapotranspiration and discharge
Keywords: Dehesa; Runoff–rainfall relationship; Semi-arid areas; Small catchment; Water budget